Three ways of looking at negative capability: William Carlos Williams, John Berryman, Mark Strand - Yurdaün, Nejat Cihan. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2014., 2014)
Negative capability, coined by the romantic poet John Keats in early 19th Century, is a significant literary concept which defines the creative process and provides tentative guidelines determining the relation between a poet and his/her poems. Although the concept belongs to the romantic period, it has been appropriated and interpreted by many modern critics and poets. This study aims to show that during specific periods in their careers three 20th century American poets - William Carlos Williams, John Berryman and Mark Strand - present three different ways of looking at negative capability. In this context, terms, concepts and theories which are linked to negative capability such as subjectivity, mimesis, autobiographical writing and objectivity as well as imagism, deconstruction and post-structuralism are also questioned and examined. This dissertation is the product of close reading of selected poems by the three poets and it demonstrates that the concept of negative capability remains a valid approach to the analysis of poetry because it highlights certain limits of poetic expression and creativity.